Faktor-Faktor Penyebab Pertumbuhan Hunian Liar Disekitar Sungai Pampang Kelurahan Panaikang Kecamatan Panakkukang Kota Makassar - Waroka, Desy; Latief, Rudi; Jufriadi (Journal of Urban Planning Studies, 2023)
This study aims to identify and determine the factors causing the growth of wild dwellings around the Pampang River, Panaikang Village, Panakkukang District, Makassar City. This study uses quantitative methods while the variables in this study consist of four of them: (1) Length of Stay; (2) Economics; (3) Infrastructure; (4) Land Status. This research analysis tool uses chis-square analysis methods and profit contingency tests to determine the correlation between variables in concluding to determine the level of relationship measured with the Likert Scale scoring system. This study's results show that economic factors are very influential factors in the growth of wild dwellings at the research site.